1996
DOI: 10.1128/jcm.34.12.2968-2972.1996
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance for Vibrio cholerae O1 and vibriophages in sewage water as a potential tool to predict cholera outbreaks

Abstract: The 1991 Peruvian cholera epidemic has thus far been responsible for 600,000 cholera cases in Peru. In an attempt to design a cholera surveillance program in the capital city of Lima, weekly sewage samples were collected between August 1993 and May 1996 and examined for the presence of Vibrio cholerae O1 bacteria and V. cholerae O1 bacteriophages (i.e., vibriophages). During the 144 weeks of surveillance, 6,323 cases of clinically defined cholera were recorded in Lima. We arbitrarily defined an outbreak as fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…V. cholerae strain 0139 was the causative agent of a waterborne epidemic of cholera in south India (Ramakrishna et al, 1996). Routine monitoring of wastewater samples for V. eholerae 01 and vibriophages was useful in predicting and controlling the outbreak of cholera in Peru, where the disease has been epidemic since 1991 (Madico et al, 1996). Dalsgaard et al (1996) compared a commercial biochemical kit (API 20E) with an oligonucleotide probe for the identification of V. vulnificus from environmental samples.…”
Section: Bacteria: Pathogensmentioning
confidence: 99%
“…V. cholerae strain 0139 was the causative agent of a waterborne epidemic of cholera in south India (Ramakrishna et al, 1996). Routine monitoring of wastewater samples for V. eholerae 01 and vibriophages was useful in predicting and controlling the outbreak of cholera in Peru, where the disease has been epidemic since 1991 (Madico et al, 1996). Dalsgaard et al (1996) compared a commercial biochemical kit (API 20E) with an oligonucleotide probe for the identification of V. vulnificus from environmental samples.…”
Section: Bacteria: Pathogensmentioning
confidence: 99%
“…Although no comprehensive studies have been carried out to look for V. cholerae O1‐ and O139‐specific phages in freshwater environments in Kolkata, to our knowledge, this is the first study to prove that the surveillance of vibriophages reveals the presence of V. cholerae O1 and O139, in particular, in the water bodies in and around Kolkata even if there is no clinical cholera cases caused by V. cholerae O139. It should be mentioned here that several earlier works have been reported on the relationship between environmental cholera phages and seasonal epidemics of cholera (Madico et al , 1996; Faruque et al , 2005a, b; Jensen et al , 2006).…”
Section: Discussionmentioning
confidence: 96%
“…In particular, epidemics of Vibrio cholerae are most well known to be associated with contaminated water sources (Acosta et al 2001;Beatty et al 2004). Moreover, active surveillance for V. cholerae O1 and vibriophages in sewage water has been shown to be a potentially useful tool to predict cholera outbreaks (Madico et al 1996). Although the significance of Aeromonas in drinking water with respect to the occurrence of acute gastroenteritis remains debatable (Leclerc et al 2002), cases of water-related infections have been reported (Filler et al 2000).…”
Section: Discussionmentioning
confidence: 99%